The role of phosphonate speciation on the inhibition of barium sulfate precipitation - Jones, Franca; Stanley, A.; Oliveira, Allan; Rohl, Andrew; Reyhani, Manijeh; Parkinson, Gordon; Ogden, Mark (Elsevier Science, 2003)
The inhibition of barium sulfate precipitation in the presence of phosphonate containing molecules was investigated experimentally and speciation curves were used to elucidate the interactions involved. Inhibition of precipitation was found to be pH dependent and loss of inhibition was observed at both very high and low pHs. Maximum inhibition for all the inhibitor molecules occurred at pH 8. While speciation curves showed that inhibition could be improved by the presence of 2 or more fully de-protonated phosphonate groups (for pure aminophosphonates) on the molecule at pH 8, at pH 12 inhibition was insensitive to the number of de- protonated phosphonate groups. It is, therefore, suggested that surface charge repulsion affects inhibition at very high pH. For molecules which are not pure aminophosphonates, stereochemistry as well as functional groups and their ionisation state appear to play a significant role in inhibition at 3<pH8.